2021
DOI: 10.3390/f12060730
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Heat Treatment of Wood: Study of Induced Effects on Ayous Wood (Triplochiton scleroxylon K. Schum)

Abstract: High-temperature treatment of wood is a useful method for improving certain physical characteristics, ensuring durability without biocides, and improving the performance of wood when exposed to degradation agents. This work aims to determine the effects induced by a heat treatment performed industrially on ayous wood (Triplochiton scleroxylon K. Schum) from Cameroon, through the study of the main physical and mechanical characteristics. The heat treatment at 215 °C for three hours with a slight initial vacuum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The results indicated that mechanical properties of heat-treated wood samples such as MOR and impact strength were decreased compared to the control samples but MOE did not decrease considerably. These findings are consistent with the results of previous studies (Hill 2006;Yildiz et al 2006;Zhao et al 2019;Gennari et al 2021). Reduction of mechanical properties is mainly attributed to the thermal degradation of wood chemical components (Taghiyari et al 2020).…”
Section: Densitysupporting
confidence: 93%
See 1 more Smart Citation
“…The results indicated that mechanical properties of heat-treated wood samples such as MOR and impact strength were decreased compared to the control samples but MOE did not decrease considerably. These findings are consistent with the results of previous studies (Hill 2006;Yildiz et al 2006;Zhao et al 2019;Gennari et al 2021). Reduction of mechanical properties is mainly attributed to the thermal degradation of wood chemical components (Taghiyari et al 2020).…”
Section: Densitysupporting
confidence: 93%
“…Decreasing the equilibrium moisture content (EMC) of the wood during heat treatment is another reason for reduced density (Kozakiewicz et al 2019). The main reason for the decrease in moisture content of heat-treated wood at high temperatures is the modification of the wood polymer structure arrangement and the possible softening of lignin (Marcon et al 2021), decrease of wood carbohydrates content as a result of decomposition of a large part of wood cell wall hemicelluloses (Gennari et al 2021), and increase in lignin's proportional content (Abreu et al 2008) that ultimately results in reduction of the wood ability to absorb water and decrease of the equilibrium moisture content of wood (Brito et al 2008).…”
Section: Densitymentioning
confidence: 99%
“…The wood types treated at 170, 190, and 210 °C became tiny cracks and collapsed on the cell wall. These defects could negatively affect the mechanical properties of the heat-treated woods (Xing et al 2016;Chen et al 2020) and also the mechanical properties of beech wood were lower than in Uludag fir wood due to highdensity loss and thermal degradation caused by complex structure and wood constitutes of hardwoods (De Oliveira Araújo et al 2016;Gennari et al 2021). The deformation and strain distribution that occurred in the bending test of heat-treated and un-treated woods were investigated with the DIC method as given in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies on thermal and charring treatments of wood showed decreases in wood densities due to chemical modifications in the wood (Metsä-Kortelainen et al 2006;Boonstra et al 2007;Gündüz et al 2008;Akyildiz et al 2009;Gunduz et al 2009;Won et al 2012;Percin et al 2016;Antons et al 2018;Kapidani et al 2019;Chotikhun et al 2020;Wang et al 2020;Esteves et al 2021;Gennari et al 2021;Ninane et al 2021;Šeda et al 2021;Taraborelli et al 2022). Hill et al (2021) showed that thermal treatments for heat-modified wood generally resulted in increased mass loss and decreased wood density due to chemical degradation and that weight loss after heat treatment was generally linked to a reduction in density associated with treatment conditions and wood species (Pfriem et al 2009).…”
Section: Resultsmentioning
confidence: 99%